Semantic context improves speech intelligibility and reduces listening effort for listeners with hearing impairment. (3rd July 2018) - Holmes, Emma; Folkeard, Paula; Johnsrude, Ingrid S.; Scollie, Susan
Abstract: Objective : We investigated whether speech intelligibility and listening effort for hearing-aid users is affected by semantic context and hearing-aid setting. Design : Participants heard target sentences spoken in a reverberant background of cafeteria noise and competing speech. Participants reported each sentence verbally. Eight participants also rated listening effort after each sentence. Sentence topic was either the same as, or different from, the previous target sentence. Study sample : Twenty participants with sensorineural hearing loss were fit binaurally with Signia receiver-in-the-canal hearing aids. Participants performed the task twice: once using the hearing aid's omnidirectional setting and once using the "Reverberant Room" setting, designed to aid listening in reverberant environments. Results : Participants achieved better speech intelligibility for same-topic than different-topic sentences, and when they used the "Reverberant Room" than the omnidirectional hearing-aid setting. Participants who rated effort showed a reliable reduction in listening effort for same-topic sentences and for the "Reverberant Room" hearing-aid setting. The improvement in speech intelligibility from semantic context (i.e. same-topic compared to different-topic sentences) was greater than the improvement gained from changing hearing-aid setting. Conclusions : These findings highlight the enormous potential of cognitive (specifically, semantic) factors for improving speech intelligibility and reducing perceived listening effort in noise for hearing-aid users.